Distribusi Spasial Kasus Demam Berdarah Dengue (DBD) di Kabupaten Dharmasraya berdasarkan Karakteristik Wilayah: Distribution of Dengue Hemorrhagic Fever (DHF) Cases in Dharmasraya Regency based on Regional Characteristics - Hayati, Nikmatul; Masrizal, Masrizal; Markolinda, Yessy (JURNAL ILMU DAN TEKNOLOGI KESEHATAN TERPADU, 2025)
Dharmasraya Regency recorded the second highest Case Fatality Rate (CFR) of Dengue Hemorrhagic Fever (DHF) in West Sumatra in 2024, alongside an Incidence Rate (IR) more than three times greater than the previous year with cases clustered in specific subdistricts. This study aimed to map the spatial distribution of DHF cases according to regional characteristics to inform targeted, area-based control policies. A quantitative descriptive design was employed using secondary data from 11 subdistricts, analyzed through univariate and spatial methods. Findings revealed that the DHF cases were highly concentrated in Sitiung, Pulau Punjung, and Koto Baru. Spatial analysis showed higher case counts in areas with higher population density, higher migration, more health facilities, and larger settlement areas. Consequently, dengue control efforts should prioritize these high-risk areas by strengthening surveillance, community education, health service capacity, integration of migration data into early warning systems, and cross-sectoral collaboration on settlement management and risk-based spatial planning.